UJI Genotipe Padi Lokal dari Aceh Barat dan Selatan untuk Ketahanan terhadap Penyakit Hawar Daun Bakteri pada Fase Generatif - Wira Hadianto; Yusrijal; Nana Ariska; Sumeinika Fitria Lizmah; Jekki Irawan; Chairudin; Agustinur; Evi Julianita Harahap (Jurnal Penelitian Pendidikan IPA, 2026)
Local rice germplasm is a valuable genetic resource for developing bacterial leaf blight (BLB)-resistant and high-yielding rice cultivars. However, information on the resistance of Southwest Aceh local rice to Xanthomonas oryzae pv. oryzae (Xoo), particularly during the generative stage, remains limited. Previous studies have mainly focused on commercial cultivars or vegetative-stage screening, leaving the resistance potential of local germplasm at the reproductive stage largely unexplored. This study aimed to evaluate the resistance of local rice to BLB at the generative stage of plant growth. The research was conducted at Experimental Field, Teuku Umar University. West Aceh (4°08′33″ N; 96°11′54″ E). Fifteen local rice genotypes, together with resistant and susceptible control varieties, were evaluated following artificial inoculation with Xoo strain VIII. Disease resistance was assessed based on incubation period and lesion length, while agronomic performance was evaluated using key yield-related traits. Seven local genotypes Itam Tangke Lango, Jantong, Jempa Puteh, Manyam U, Pade Manggeng-1, Pade Manggeng-2, and Rangan Lango were classified as resistant based on lesion length. Among the evaluated genotypes, Sikleng exhibited superior agronomic performance, producing the highest number of productive tillers (27.50) and grains per panicle (317.73). The novelty of this study lies in evaluating Southwest Aceh local rice germplasm for bacterial leaf blight resistance at the generative stage using Xoo strain VIII while integrating disease resistance with yield-related agronomic traits. The identified resistant genotypes provide valuable donor parents for breeding BLB-resistant, high-yielding rice cultivars and contribute to sustainable rice production and regional food security.